THE ANALYSIS OF CONSUMER PREFERENCES OF PRICE ENDINGS AT HYPERMART MANADO TOWN SQUARE - Beyah, Friska Anggreiny (FEB Universitas Sam Ratulangi Manado, 2013)
Price has become one important consideration for many businessmen or marketers in selling products or providing services for people in marketplace. Therefore, this research is purposed to know the analysis of consumer preferences of price endings at Hypermart Manado Town Square. This research uses qualitative method analysis, while interview and questionnaire will be data collection method. Informant is taken from people who have visited Hypermart Manado Town Square. The sample of this research is 30 customers of Hypermart. There is one important finding that can be concluded from the overall result in this research, which is; the similar perception of Consumer Behavior, Brand ,and Price Ending about electronic devices and how customers make their perception about purchasing and using this specified products. It is understandable that an ideal understanding of the consumer behavior is important in encouraging customers to choose the appropriated electronic products in Manado. Customers in Manado give the in-depth consideration for the Brand and Price Endings for electronic products in Manado. Keywords: price endings, consumer preferences